1981
DOI: 10.1038/bjc.1981.70
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage content and colony-forming potential in mouse mammary carcinomas

Abstract: Summary.--The macrophage content of cell suspensions from naturally occurring mouse tumours has been assessed by the Fc-mediated phagocytosis assay, and the results compared with the individual tumour's capacity for spontaneous metastasis and with its pulmonary colonization potential after i.v. inoculation.It was found that these tumours differ in their properties from the transplantable fibrosarcomas studied previously by other investigators, in that the macrophage content of all the tumours was uniformly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…It has been suggested that the presence of macrophages may independently influence the outcome by affecting the metastatic potential of tumours (Lauder et al, 1977) and there is evidence from experimental animal tumours that this is so (Fidler & Poste, 1982;Eccles & Alexander, 1974; Wood & Gillespie, 1975). However, others have found otherwise; for example, in the case of murine mammary carcinoma (Nash et al, 1979). In vitro studies have shown a tumoricidal effect of human macrophages on a variety of human tumour lines including mammary carcinoma (Sone et al, 1984(Sone et al, , 1985.…”
mentioning
confidence: 93%
“…It has been suggested that the presence of macrophages may independently influence the outcome by affecting the metastatic potential of tumours (Lauder et al, 1977) and there is evidence from experimental animal tumours that this is so (Fidler & Poste, 1982;Eccles & Alexander, 1974; Wood & Gillespie, 1975). However, others have found otherwise; for example, in the case of murine mammary carcinoma (Nash et al, 1979). In vitro studies have shown a tumoricidal effect of human macrophages on a variety of human tumour lines including mammary carcinoma (Sone et al, 1984(Sone et al, , 1985.…”
mentioning
confidence: 93%
“…Moreover, detailed studies on the activated macrophage content of spontaneously-occurring mammary carcinomas in mice showed no correlation with either spontaneous metastatic capability of the tumor nor with the capacity of its cells to colonize downstream organs after intravascular injection [57]. However, it should be mentioned that recently published data [58] have indicated that tumor associated macrophages (TAM) can diminish the efficacy of chemotherapeutic agents and that drugs blocking the cathepsin activity TAM improved the anti-tumor activity of the cytotoxic agents.…”
Section: Inflammation and Cancermentioning
confidence: 96%
“…Little, however, is known about the role of macrophages within metastases once the tumor has become established. The failure of the host to 85 inhibit metastatic growth may be related to qualitative (10,47) or quantitative (3) deficiencies in macrophages infiltrating metastases. Conceivably such a deficiency could allow metastases to circumvent host defense mechanisms and grow progressively.…”
Section: Discussionmentioning
confidence: 99%
“…Still other studies have reported that metastases contain fewer macrophages than the primary tumors from which they originate (3). Conceivably, a deficiency in macrophage infiltration of metastases could allow these tumors to circumvent host defense mechanisms and grow progressively, although, again, these generalizations have not been confirmed (10,14,15). Thus, the role of macrophages in control of metastatic growth is far from clear.…”
Section: Introductionmentioning
confidence: 99%